2019
DOI: 10.3390/plants8110519
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Endogenous Hormones on the Flowering and Fruiting of Glycyrrhiza uralensis

Abstract: Although endogenous hormones play an important role in flower bud differentiation and seed-filling, their effects on the flowering and fruiting of Glycyrrhiza uralensis Fisch. remain unknown. In the present study, we investigate the differences in the levels of endogenous hormones gibberellic acid (GA), abscisic acid (ABA), zeatin riboside (ZR), and indoleacetic acid (IAA) between the fruiting and seedless plants of G. uralensis Fisch. at different growth stages. We also determine the correlations of the endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Due to excessive excavation and habitat destruction in recent years, wild resources of Chinese herbal medicines are very limited in nature. Overharvesting has gradually exhausted wild resources, and cultivated G. uralensis has become an alternative source 34 . However, practices and studies have indicated that the salt tolerance of cultivated G. uralensis is lower than that of wild plants 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to excessive excavation and habitat destruction in recent years, wild resources of Chinese herbal medicines are very limited in nature. Overharvesting has gradually exhausted wild resources, and cultivated G. uralensis has become an alternative source 34 . However, practices and studies have indicated that the salt tolerance of cultivated G. uralensis is lower than that of wild plants 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed the differential expression of phytohormones especially GA and ABA during seed germination and growth of seedlings. ABA was found to be lower during seed germination stage and early seedling developmental stages and negatively correlated with seed filling 43 and elongation of internodes 44 , however, ABA increases when the growth of the plant ceases 43 . GA was positively correlated with elongation during internodal development 44 .…”
Section: Discussionmentioning
confidence: 90%
“…Among them, K fertilizer increased the IAA, GA, and ZR contents and decreased the ABA 3 content (Tu et al, 2017). Our research shows that IAA, GA, and ZR are beneficial to the 3 flower bud differentiation and seed filling, while ABA was not beneficial (Yan et al, 2019). 3 Therefore, N, P, and K fertilizers may affect the seed yield by affecting the content of 3 endogenous hormones in licorice plants.…”
mentioning
confidence: 75%